2011
DOI: 10.1098/rstb.2010.0297
|View full text |Cite
|
Sign up to set email alerts
|

Parental investment and the optimization of human family size

Abstract: Human reproductive behaviour is marked by exceptional variation at the population and individual level. Human behavioural ecologists propose adaptive hypotheses to explain this variation as shifting phenotypic optima in relation to local socioecological niches. Here we review evidence that variation in fertility (offspring number), in both traditional and modern industrialized populations, represents optimization of the life-history trade-off between reproductive rate and parental investment. While a reliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 96 publications
(184 reference statements)
12
126
0
Order By: Relevance
“…Among the first to adopt the use of modern contraception are those farmers who have inherited the smallest parcels of land (β − 0.61 ± 0.28, P = 0.032; Table 2). These findings contribute to growing evidence that competition for inelastic heritable resources, such as land, cattle, and titles, represents an important determinant of the nature of sibling relationships and also parental reproductive decision making (6,19).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Among the first to adopt the use of modern contraception are those farmers who have inherited the smallest parcels of land (β − 0.61 ± 0.28, P = 0.032; Table 2). These findings contribute to growing evidence that competition for inelastic heritable resources, such as land, cattle, and titles, represents an important determinant of the nature of sibling relationships and also parental reproductive decision making (6,19).…”
Section: Discussionmentioning
confidence: 93%
“…Recent anthropological studies in pretransitional societies, however, have found mixed evidence of adult sibling resource competition (19). In some instances positive effects of siblings have been demonstrated, suggesting that the costs to resource division within the family have the potential to be offset by beneficial cooperative activities between siblings (see reviews of human cooperative breeding strategies in refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, such cultural inheritance patterns would be interpreted as simply one mechanism through which our species adapts its behaviour to the local ecology, but this human behavioural ecology perspective also does not necessarily preclude the notion that such cultural inheritance patterns could potentially operate independently of the influences of ecological variables. For example, human behavioural ecologists have successfully applied optimality modelling to recent life-history changes, such as low fertility in postdemographic populations [75], despite the suggestion that post-industrial cultural change has occurred too quickly to avoid a 'mismatch' or 'adaptive lag' between the environment and our evolved behavioural strategies. Incorporating socially learned transmission of information is therefore not inevitably incongruent with the human behavioural ecology perspective [76,77].…”
Section: Integrating Evolutionary Perspectives On Human Behaviourmentioning
confidence: 99%
“…Likewise, in many cases, the evolutionary and the mainstream approaches are quite similar. For example, the quantity-quality offspring trade-off is quite similar in certain areas of demography and evolutionary anthropology [16,[63][64][65]. The role of cultural norms, and how they spread, is an emerging area of study in both social demography and evolutionary demography [34,45,66], which makes it an area of potential collaboration between fields.…”
Section: Synopsis and Conclusionmentioning
confidence: 99%